Elements for mathematical modeling in pneumonia epidemiology - Gómez Hernández, Enith A.; González Santacruz, Elisa C.; Ibarguen Mondragón, Eduardo (Universidad y Salud, 2014)
Pneumonia is an acute respiratory infection (ARI) which affects the lungs. It is considered as the second cause of death associated with respiratory infections globally. In Colombia, there are reports of approximately 120,000 consultations per year and 50,000 hospital discharges in children under 5. In particular, in the municipality of San Juan de Pasto, there were 65 deaths associated with this disease in 2010. It can be contributed directly to the study of the distribution, causation and prevention of the disease through mathematical modeling about pneumonia epidemiology. The purpose of this review is to relate pneumonia epidemiology with mathematical modeling.